Study Effect of Aloe Vera Gel on Lice Parasite of Laying Hens - A. Shlash, Shaimaa; Hussein A. Kadhum, M.SC. (International Journal of Psychosocial Rehabilitation, 2020)
Aimed this study to be evaluated of Aloe vera gel extraction effect on lice parasite in laying hens, were conducted in the duration from March 2019 to August 2019. Use in the now study 40 laying hens, shows positive significant correlation between the number of concentrations 2, 3, 4gm/ ml-1 respectively and number of birds after heal, total healing rate of birds were 52% after the skin was wiped by extraction of Aloe vera gel compared with control group were 0% after three weeks for three times a day. Significant increase showed in the PCV, Hb, RBC and WBC count in third week when the concentration 4 gm/ml-1 compares with control in treated of the birds. As showed significantly reduction in total cholesterol rate (p<0.05) in three weeks after treated with gel compared with the control, total protein (p<0.05) values showed significantly rise compare with the control and ALP (P<0.05) levels showed significant decline in the plasma in the third week when the concentration 4 gm/ml-1 in three weeks after treated compared with the control. These results demonstrated that Aloe veragel extract had significant effects on the hematological and biochemical parameters and inhibitory effect against lice parasite in the laying hens.